(untitled) (Indonesian Court and Justice Review, 2024)
The principle of equality before the law is a cornerstone of any just legal system, yet instances of discrimination in criminal court rulings persist, raising concerns about the fairness and impartiality of judicial processes. This study empirically examines whether discrimination exists in criminal court rulings, investigating how factors such as race, gender, socio-economic status, and ethnicity may influence judicial decisions. The research utilizes a comprehensive analysis of criminal case data, combined with qualitative interviews of legal professionals, defendants, and advocates, to identify patterns and assess whether biases manifest in sentencing, verdicts, and legal interpretations. The findings reveal that, while the legal framework formally guarantees equal treatment, significant disparities exist in the application of justice, with certain groups facing harsher outcomes than others. The novelty of this study lies in its empirical approach, which provides concrete evidence of discrimination within the criminal justice system, offering a deeper understanding of its structural and procedural causes. This research is urgent given the global calls for judicial reform and the increasing awareness of systemic biases in legal institutions. By contributing to the ongoing discourse on fairness and equality in the justice system, this study offers both insights into the causes of discrimination in criminal rulings and recommendations for policy reforms aimed at ensuring justice for all, regardless of personal characteristics or background.